# math

lim (7-6x^5)/(x+3)....
the lim is x->+infinity
[ans=-infinity but i get 0]
can someone show me the calculation work.

1. 👍 0
2. 👎 0
3. 👁 65
1. dividing the expression results in a leading term of
-6x^4
as x --> + infinity
-6x^4 ---> - infinity

1. 👍 0
2. 👎 0
posted by Reiny

## Similar Questions

1. ### calc

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity? and lim x->0- = + infinity? lim x->1 (x^2 - 5x + 6)/(x^2 - 3x + 2) I get 2/0, so lim x-> 1+ = - infinity? and lim x->1- = +

asked by Chelsea on October 13, 2010

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity? and lim x->0- = + infinity? lim x->1 (x^2 - 5x + 6)/(x^2 - 3x + 2) I get 2/0, so lim x-> 1+ = - infinity? and lim x->1- = +

asked by Chelsea on October 14, 2010
3. ### Calc. Limits

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity? and lim x->0- = + infinity? lim x->1 (x^2 - 5x + 6)/(x^2 - 3x + 2) I get 2/0, so lim x-> 1+ = - infinity? and lim x->1- = +

asked by Chelsea on October 13, 2010
4. ### calculus

State which of the conditions are applicable to the graph of y = f(x). (Select all that apply.) lim x→infinity f(x) = −infinity lim x→a+ f(x) = L lim x→infinity f(x) = L f is continuous on [0, a] lim x→infinity f(x) = 0

asked by Lyric on September 22, 2011
5. ### Math

Find the limit if it exists. lim 1/(x-2) = infinity x→2+ lim 1/(x-2) = negative infinity x→2- lim 1/(x-2) = Does not exist x→2 lim (3x+2) = infinity x→∞ lim 999/(x^3) = 0 x→-∞ Can someone check to make sure that I am

asked by David on May 19, 2016
6. ### Calculus Limits

Question: If lim(f(x)/x)=-5 as x approaches 0, then lim(x^2(f(-1/x^2))) as x approaches infinity is equal to (a) 5 (b) -5 (c) -infinity (d) 1/5 (e) none of these The answer key says (a) 5. So this is what I know: Since

asked by Anonymous on March 2, 2019
7. ### calculus - ratio test

infinity of the summation n=1: (e^n)/(n!) [using the ratio test] my work so far: = lim (n->infinity) | [(e^n+1)/((n+1)!)] / [(e^n)/(n!)] | = lim (n->infinity) | [(e^n+1)/((n+1)!)] * [(n!)/(e^n)] | = lim (n->infinity) |

asked by COFFEE on July 30, 2007
8. ### Calculus - ratio test

infinity of the summation n=1: (e^n)/(n!) [using the ratio test] my work so far: = lim (n->infinity) | [(e^n+1)/((n+1)!)] / [(e^n)/(n!)] | = lim (n->infinity) | [(e^n+1)/((n+1)!)] * [(n!)/(e^n)] | = lim (n->infinity) |

asked by COFFEE on July 29, 2007
9. ### math

i really don't understand why this 1-lim 3/(y+4) [the lim is x->infinity] the ans is 0 while this 2-lim (7-6x^5)/(x+3) [x->+infinity ] is - infinity. can anyone explain why the 1 is zero & the 2 is infinity.

asked by susan on July 20, 2011
10. ### Calculus

Show that limit as n approaches infinity of (1+x/n)^n=e^x for any x>0... Should i use the formula e= lim as x->0 (1+x)^(1/x) or e= lim as x->infinity (1+1/n)^n Am i able to substitute in x/n for x? and then say that e lim x ->0

asked by Frederick E. on November 8, 2011
11. ### Calculus

Show that limit as n approaches infinity of (1+x/n)^n=e^x for any x>0... Should i use the formula e= lim as x->0 (1+x)^(1/x) or e= lim as x->infinity (1+1/n)^n Am i able to substitute in x/n for x? and then say that e lim x ->0

asked by Frederick E. on November 9, 2011

More Similar Questions